Конфлікт цінностей на підприємстві в інформаційному суспільстві - Лінькова, Олена Юріївна (НТУ "ХПІ", 2018)
В роботі проаналізовано особливості становлення інформаційного суспільства в Україні. Проведено аналіз категорії цінності та конфлікту цінностей. Виділено переваги та ризики ціннісного управління. Запропоновані компенсатори в менеджменті ризиків зміни цінностей у персоналу. Наведено класифікацію правил вирішення конфліктів цінностей за внутрішньою і зовнішніми складовими. Систематизовано підходи до розвитку цінностей в інформаційному суспільстві. Запропоновано напрямки розв'язання конфлікту цінностей в бізнесі. Зазначені питання для проведення подальших досліджень.

Managing a conflict of values at an enterprise opens up new opportunities for strategic personnel development. The purpose of the work is to systematize the causes of conflicts of valuesin Ukraine in the conditions of the information society. The purpose of the publication is to establish the causal relationships between conflicts of values and business results, as well as directions for their solution. Classification of the company's norms of moral, legal and standard of expectation allows to predict the problems in the behavior of the personnel and the necessary actions for their management by managers. The main directions of solving conflicts of values in an enterprise are systematization of rules of conflict management, the establishment of norms and elements of social control over their compliance, the criterial selection of managers (according to the individual system of values and style of behavior and cooperation, motivation of the staff.) The dynamics of changing the values of a person engaged in business affects The possibility of solving value conflicts. The introduction of value management in business practice at the present stage of management in Ukraine will allow To steer innovative development at the expense of constructive behavior in the inevitable value conflicts. Directions for further research: assessment of the risks of conflict management of values, models of value management, image formation.
Conflict of values at the enterprise in the information society
Keywords: ціннісне управління; менеджмент; цінності; конфлікт; інформаційне суспільство; управління конфліктом; management; value management; values; conflict; information society; conflict management